GWAS with principal component analysis identify QTLs associated with main peanut flavor-related traits - Zhang, Hui; Dean, Lisa; Wang, Ming Li; Dang, Phat; Lamb, Marshall; Chen, Charles (Frontiers in Plant Science, 2023)
Peanut flavor is a complex and important trait affected by raw material and processing technology owing to its significant impact on consumer preference. In this research, principal component analysis (PCA) on 33 representative traits associated with flavor revealed that the first three principal components (PCs): total sugars, sucrose, and total tocopherols, provided more information related to peanut flavor. Genome wide association studies (GWAS) using 102 U.S. peanut mini core collection were performed to study associations between 12,526 single nucleotide polymorphic (SNP) markers and the three PCs. A total of seven and twenty-two significant quantitative trait loci (QTLs) were identified to be significantly associated total sugars and sucrose, respectively. Around these QTLs, four and eight candidate genes for the two traits were mined. In addition, two and five stable QTLs were identified for total sugars and sucrose in both years separately. No significant QTLs were detected for total tocopherols. Results from this research provide useful knowledge about the genetic control of peanut flavor, which will aid in clarifying the molecular mechanisms of flavor research in peanut.